2008
DOI: 10.4161/cbt.7.10.6565
|View full text |Cite
|
Sign up to set email alerts
|

Frequent genomic copy number gain and overexpression of GATA-6 in pancreatic carcinoma

Abstract: Multiple genetic alterations are well recognized as contributing to pancreatic carcinogenesis, although the finding of recurrent copy number changes indicates additional targets remain to be found. The objective of this study was to identify novel targets of genetic alteration that contribute to pancreatic cancer development or progression. We used Representational Oligonucleotide Microarray Analysis (ROMA) to identify copy number changes in pancreatic cancer xenografts, and validated these findings using FISH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 34 publications
6
67
0
Order By: Relevance
“…Interestingly, Kwei et al (36) and Fu et al (37) reported that 18q11.2 gain/amplification with overexpression of GATA6 is detected in 9-19% of pancreatic carcinomas. Both the pancreas and distal esophagus are derived from the embryonic endodermal foregut, making it plausible that these two tumors may share a common lineage-survival oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Kwei et al (36) and Fu et al (37) reported that 18q11.2 gain/amplification with overexpression of GATA6 is detected in 9-19% of pancreatic carcinomas. Both the pancreas and distal esophagus are derived from the embryonic endodermal foregut, making it plausible that these two tumors may share a common lineage-survival oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of these genes has been reported in several human cancers, including pancreatic cancer (GATA6; ref. 33), B-cell chronic lymphocytic leukemia (B-CLL) and follicular lymphoma (PRKCB; ref. 34), and liver cancer (IGFBP5; ref.…”
Section: Smchd1 Deficiency Leads To Increased Clonogenicity Of Premalmentioning
confidence: 99%
“…Such studies have led to the identification of new pancreatic cancer genes, including, for example, PAK4 (11,12) and GATA6 (13,14), validating the utility of an agnostic, genome-wide approach.…”
mentioning
confidence: 99%